2019
DOI: 10.1111/jbg.12386
|View full text |Cite
|
Sign up to set email alerts
|

“Bending” and beyond: Better estimates of quantitative genetic parameters?

Abstract: Multivariate estimation of genetic parameters involving more than a handful of traits can be afflicted by problems arising through substantial sampling variation. We present a review of underlying causes and proposals to improve estimates, focusing on linear mixed model‐based estimation via restricted maximum likelihood (REML). Both full multivariate analyses and pooling of results from overlapping subsets of traits are considered. It is suggested to impose a penalty on the likelihood designed to reduce sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Estimation of genetic parameters is a fundamental task in quantitative genetics (Meyer, 2019) As far as we know, genetic parameters of the aforementioned traits have not yet been studied in Qingyuan partridge chickens. Variance components of body weight have been widely investigated in domestic animals, and it was reported that maternal effects significantly contribute to phenotypes (Alves et al., 2018; Kushwaha et al., 2009; Roy et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of genetic parameters is a fundamental task in quantitative genetics (Meyer, 2019) As far as we know, genetic parameters of the aforementioned traits have not yet been studied in Qingyuan partridge chickens. Variance components of body weight have been widely investigated in domestic animals, and it was reported that maternal effects significantly contribute to phenotypes (Alves et al., 2018; Kushwaha et al., 2009; Roy et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There exists previous work on penalized estimation of genetic covariances (e.g., Meyer et al , 2011; Meyer, 2016, 2019) that also uses Bayesian principles and scale-free penalty functions to reduce variation of the estimates from small datasets and for large numbers of traits. Our proposed priors and expert knowledge reduced variation of estimates in the simulated case study.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could expand the hierarchical decomposition prior framework to other settings. For example, to multiple traits or modelling genotype-by-environment interactions, which are notoriously noisy, and we aim to find parsimonious models (e.g., Meyer, 2016, 2019; Tolhurst et al , 2019). Also, expand to model macro- and micro-environmental effects (e.g., Selle et al , 2019) and to model multiple layers of sparse, yet high-dimensional, “omic” data from modern biological experiments using network-like models (Damianou and Lawrence, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A parameter expanded EM algorithm (Liu, Rubin, & Wu, ) is implemented in ASReml for this case but does not quickly produce an acceptable result when the maximum of the likelihood corresponds to parameter values outside the parameter space. Meyer () presents an approach which seeks to bend a genetic variance matrix towards the covariance structure of the phenotypic variance matrix in the context of multivariate analysis. Another approach is to use a more parsimonious parameterization.…”
Section: Methodsmentioning
confidence: 99%